Implementation of Public Service Quality in BPBD Surabaya City - Desi Ayu Widya Rahma (Lavish Opulent Education, 2025)
This study aims to analyze the implementation of public service quality at the Regional Disaster Management Agency (BPBD) of Surabaya City in the context of disaster education and outreach to the community. The analysis focuses on five dimensions of the SERVQUAL model—tangibles, reliability, responsiveness, assurance, and empathy—which serve as indicators for measuring the Community Satisfaction Index (IKM). A descriptive quantitative approach was employed, using questionnaires as the primary data collection method. The respondents comprised 100 residents of Surabaya who had participated in disaster awareness programs within the past three months. The findings reveal that all five dimensions of service quality were rated in the